(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Factors Affecting Income of Inter-provincial Siam Madu Orange Traders in Karo Regency, North Sumatra. Siam madu orange collectors in Karo Regency are inter-provincial distributors of oranges which made traders make shipments in large quantities. The income of siam madu oranges traders can be influenced by various factors. The purpose of this study was to analyze the level of income and analyze the effect of selling volume, number of damaged goods, marketing costs, trading experience and average selling price on trader’s income. The sample in this study was obtained through a census of 20 traders of siam madu oranges who focused on selling outside the province of North Sumatra. The analysis technique used was income analysis and multiple linear regression analysis. The results showed that all samples had a fairly large and stable net profit and the average R/C ratio was 1,225, meaning that the trading business of siam madu orange collectors was profitable. The results of the partial test (t-test) show that selling volume (X1), trading experience (X4) partially has a positive effect on income while the number of damaged goods (X2), marketing costs (X3) partially has a negative effect on income and average selling price (X5) has no effect on income.